2019
DOI: 10.13004/kjnt.2019.15.e32
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Operation of Acute Subdural Hematoma in Subacute Stage by Trephine Drainage using Urokinase

Abstract: Objective: The principle operation of acute subdural hematoma (ASDH) is a craniotomy with hematoma removal, but a trephination with hematoma evacuation may be another method in selected cases. Trephine drainage was performed for ASDH patients in subacute stage using urokinase (UK) instillation, and its results were evaluated. Methods: Between January 2016 and December 2018, the trephine evacuation using UK was performed in 9 patients. The interval between injury and operation was from 1 to 2 weeks. We underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Kpealo et al reported onset of symptoms after trauma with ASDH after 27.4 days in case of CSDH and 12.6 days in case of subacute SDH [ 19 ]. In a study by Kang et al, 9 patients with SDH in the subacute stage were treated via burr hole trephination and injection of urokinase in patients with increased midline shift or clinical deterioration after 10.2 days of trauma with ASDH [ 15 ]. Other studies reported similar time periods with mean number of days between 11 and 18 after trauma with ASDH and burr hole trephination for liquefied subdural hematoma [ 1 , 6 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kpealo et al reported onset of symptoms after trauma with ASDH after 27.4 days in case of CSDH and 12.6 days in case of subacute SDH [ 19 ]. In a study by Kang et al, 9 patients with SDH in the subacute stage were treated via burr hole trephination and injection of urokinase in patients with increased midline shift or clinical deterioration after 10.2 days of trauma with ASDH [ 15 ]. Other studies reported similar time periods with mean number of days between 11 and 18 after trauma with ASDH and burr hole trephination for liquefied subdural hematoma [ 1 , 6 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, identifying patients at risk is beneficial for clinical monitoring of these ASDH patients, and on the other hand, knowledge about the clinical and radiographic progression from ASDH to CSDH within the days and weeks after trauma is important for monitoring and early adequate treatment of these patients. The course of these patients has only been reported in some small case series [ 1 , 6 , 15 , 19 ]. Also, limited data is available about potential differences of this form of CSDH and the conventional CSDH form which usually develops over a longer period of time [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%